Saunders dictionary & encyclopedia of laboratory medicine and technology - Bennington, James L.;Brecher, George (Philadelphia : Saunders, 1984)
Comprehensive, authoritative definitions of terminology used in laboratory medicine. Intended as a reference source for all involved health professionals and students. Includes vocabulary from all related disciplines. The definitions, reviewed before approval, were written by leading authorities, the medical editors, and dictionary staff. Also includes acronyms, symbols, eponyms, abbreviations, and taxonomic definitions. Miscellaneous appendixes, including normal values.
Keywords: Clinical Laboratory Techniques